Implementasi Pembelajaran Kitab Maḥfūẓāt dalam Pembentukan Nilai-Nilai Religius Siswa - Kamilah, Syarifah; Reksiana, Reksiana (An-Nuha, 2024)
The decline of moral values in religious education within the current educational landscape is attributed to the lack of attention from society towards instilling religious values in children from an early age. The Maḥfūẓāt textbook offers a method for shaping religious values among learners. This research aims to explore the potential of the Maḥfūẓāt textbook in strengthening the understanding and practice of religious values in daily life. This qualitative study involved the head of the madrasah, Maḥfūẓāt teachers, three sixth-grade students, and three parents of sixth-grade students as research subjects. Data collection techniques included observation, interviews, and documentation. The results indicate that the implementation and practice initiated by teachers begin with providing fundamental Maḥfūẓāt materials applicable to daily life, serving as role models, and instilling positive habits for both educators and students. Supportive factors include the educators' significant contributions to shaping students' religious values. However, obstacles include students who are unfamiliar with the Arabic alphabet, resulting in a lack of understanding of the subject matter.